Angiogenesis and the tumour hypoxia response in prostate cancer: a review. - Sooriakumaran, P; Kaba, R (2005)
The formation of new blood vessels, angiogenesis, is a highly-regulated active process that is critical for the development of the normal and malignant prostate. The vascular endothelial growth factor (VEGF) system assumes a critical role in the angiogenic process. Angiogenesis is a prerequisite for the expansion of solid tumours beyond 1-3 mm3 and is stimulated in response to a hypoxic environment. This review discusses the process of angiogenesis and the key angiogenic mediator, VEGF, and their role in tumour progression and metastasis. A better understanding of the mechanisms behind angiogenesis will ultimately lead to the development of new anti-angiogenic agents in the management of prostate cancer.